(2+1)-Dimensional Bidirectional Sawada-Kotera-Like Equation and Its Rational Types of Solutions. Issue 1 (1st December 2022) - Lin, Xu; Zhou, Fan; Jiang, Kun; Li, Wenting
Abstract: In this paper, a new (2+l)-dimensional bidirectional Sawada-Kotera-like (BSK-like) equation is constructed by utilizing the generalized Hirota bilinear differential operators with third order. By using the Hirota bilinear method, some rational types of the solutions, especially lump-type solutions of the BSK-like equation, are obtained with the help of the software Maple. The characteristic and dynamic states of the lump-type solutions and the rational-type solutions to the BSK-like equation are shown by plotting with some special values.